Using Open Public Meetings and Elections to Promote Inward Transparency and Accountability: Lessons From Zambia - Taryn Vian; Rachel M. Fong; Jeanette L. Kaiser; Misheck Bwalya; Viviane I.R. Sakanga; Thandiwe Ngoma; Nancy A. Scott (Kerman University of Medical Sciences, 2022)
BackgroundCommunity-led governance can ensure that leaders are accountable to the populations they serve and strengthen health systems for maternal care. A key aspect of democratic accountability is electing respective governance bodies, in this case community boards, and holding public meetings to inform community members about actions taken on their behalf. After helping build and open 10 maternity waiting homes (MWHs) in rural Zambia as part of a randomized controlled trial, we assisted community governance committees to plan and execute annual meetings to present performance results and, where needed, to elect new board members.MethodsWe applied a principally qualitative design using observation and analysis of written documentation of public meetings to answer our research question: how do governance committees enact inward transparency and demonstrate accountability to their communities. The analysis measured participation and stakeholder representation at public meetings, the types and purposes of accountability sought by community members as evidenced by questions asked of the governance committee, and responsiveness of the governance committee to issues raised at public meetings.ResultsPublic meetings were attended by 6 out of 7 possible stakeholder groups, and reports were generally transparent. Stakeholders asked probing questions focused mainly on financial performance. Governance committee members were responsive to questions raised by participants, with 59% of answers rated as fully or mostly responsive (showing understanding of and answering the question). Six of the 10 sites held elections to re-elect or replace governance committee members. Only 2 sites reached the target set by local stakeholder committees of 50% female membership, down from 3 at formation. To further improve transparency and accountability, community governance committees need to engage in advance preparation of reports, and should consult with stakeholders on broader measures for performance assessment. Despite receiving training, community-level governance committees lacked understanding of the strategic purpose of open public meetings and elections, and how these relate to democratic accountability. They were therefore not motivated to engage in tactics to manage stakeholders effectively. ConclusionWhile open meetings and elections have potential to enhance good governance at the community level, continuous training and mentoring are needed to build capacity and enhance sustainability.